2017
DOI: 10.1039/c7ta07934f
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional NH2-MIL-88(Fe) metal–organic framework nanooctahedra for highly sensitive detection and efficient removal of arsenate in aqueous media

Abstract: Bifunctional NH2-MIL-88(Fe) nanooctahedra have been successfully fabricated for highly sensitive and specific recognition as well as efficient removal of arsenate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(93 citation statements)
references
References 60 publications
8
85
0
Order By: Relevance
“…Metal-organic frameworks (MOFs) have long been a new class of porous nanomaterials because of their adjustable porosity and rich organic elements. [16,17] Bulk oxygen defects are formed by in situ carbon reduction of carbon elements in MOFs, and the formed carbon skeleton can also be used as a conductive network.…”
Section: In Recent Years Rechargeable Aqueous Zinc-ion Batteries (Zimentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) have long been a new class of porous nanomaterials because of their adjustable porosity and rich organic elements. [16,17] Bulk oxygen defects are formed by in situ carbon reduction of carbon elements in MOFs, and the formed carbon skeleton can also be used as a conductive network.…”
Section: In Recent Years Rechargeable Aqueous Zinc-ion Batteries (Zimentioning
confidence: 99%
“…The spectrum of MIL-88(Fe) is in accord with previously reported works. [36] The strong bands at 1600 cm À 1 and 1394 cm À 1 are due to the asymmetric and symmetric stretching vibration modes of the OÀ CÀ O in the MIL-88(Fe), [37] which indicates the existence of the dicarboxylate linker in the resultant framework structure. Meanwhile, the obvious peak at 550 cm À 1 is related to the Fe-O vibration, and some strong bands still could be found in the spectrum of PPy NSs that were same with the pure MIL-88(Fe), demonstrating that decomposition of MIL-88(Fe) was incomplete.…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic as a representative anionic species could be effectively adsorbed by Fe‐MOFs. Xie et al reported the extraordinary adsorption performance for using NH 2 ‐MIL‐88(Fe) to remove arsenate from aqueous media . NH 2 ‐MIL‐88(Fe) crystals can achieve a saturated arsenate sorption capacity of 125 mg g −1 through a chemical adsorption process.…”
Section: Applicationsmentioning
confidence: 99%
“…The rising development of MOFs in chemistry and material science is related to the unique topological structure and the exploitable properties for various applications. MOFs are currently arousing great interest in molecular sensing, battery, catalysis, gas adsorption and separation, biomedicine, drug delivery, template material, and pesticide testing …”
Section: Introductionmentioning
confidence: 99%